2005
DOI: 10.1590/s0103-90162005000400010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of cultivated Coffea arabica inbred lines assessed by RAPD, AFLP and SSR marker systems

Abstract: One of the greatest problems in Coffea arabica breeding is identifying precisely any inbred line, based only on botanical and agronomical descriptors, because of the reduced genetic variability of the species, close pedigree origin, which results in small phenotypic variation. Recently, molecular markers have been used for plant germplasm characterization and identification in several commercial species. This work evaluates the reliability of three marker systems: RAPD, AFLP and SSR, to characterize the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 24 publications
4
59
2
7
Order By: Relevance
“…Nilai rata-rata jumlah alel per lokus dan jumlah total alel yang diperoleh pada penelitian ini lebih tinggi dibandingkan dengan penelitian sebelumnya yang dilakukan oleh Teressa et al (2010), yaitu 6,5 alel per lokus dengan jumlah total 200 alel pada 133 aksesi kopi Arabika dengan menggunakan 32 marka SSR. Sementara, Maluf et al (2005) yang melakukan penelitian pada 28 kultivar kopi Arabika menggunakan 23 marka SSR mendapatkan jumlah total 65 alel dengan rata-rata 2,87 alel per lokus. Perbedaan nilai rata-rata jumlah alel per lokus dan jumlah total alel tersebut diduga dipengaruhi oleh perbedaan jumlah dan jenis kultivar, serta perbedaan jumlah marka SSR yang digunakan.…”
Section: Analisis Dataunclassified
See 1 more Smart Citation
“…Nilai rata-rata jumlah alel per lokus dan jumlah total alel yang diperoleh pada penelitian ini lebih tinggi dibandingkan dengan penelitian sebelumnya yang dilakukan oleh Teressa et al (2010), yaitu 6,5 alel per lokus dengan jumlah total 200 alel pada 133 aksesi kopi Arabika dengan menggunakan 32 marka SSR. Sementara, Maluf et al (2005) yang melakukan penelitian pada 28 kultivar kopi Arabika menggunakan 23 marka SSR mendapatkan jumlah total 65 alel dengan rata-rata 2,87 alel per lokus. Perbedaan nilai rata-rata jumlah alel per lokus dan jumlah total alel tersebut diduga dipengaruhi oleh perbedaan jumlah dan jenis kultivar, serta perbedaan jumlah marka SSR yang digunakan.…”
Section: Analisis Dataunclassified
“…Oleh sebab itu, perlu dianalisis kekerabatan genetik kultivar AGK-1 dengan kultivar lain yang diduga sebagai tetuanya. Pendekatan yang dapat digunakan untuk menganalisis kekerabatan genetik kultivar kopi Arabika adalah melalui pemanfaatan teknologi marka molekuler, seperti marka random amplified polymorphic DNA (RAPD) dan simple sequence repeat (SSR) yang diketahui dapat mengelompokkan kultivar kopi Arabika sesuai dengan asal-usul genetiknya (Maluf et al, 2005).…”
unclassified
“…Considering that the coffee genotypes evaluated in this study originated from diferent countries (Kenya, Puerto Rico, Tanzania, Ethiopia, Reunion, Portugal, Yemen, Guatemala and Colombia), the similarities observed among Arabica genotypes, attests to the narrow genetic diversity among cultivated Arabica coffee reported in other studies (Lashermes et al, 1993). Comparatively, higher genetic diversity has been reported among wild coffee populations than within cultivated genotypes Aga et al, 2003;Masumbuko et al, 2003;Masumbuko and Bryngelsson 2006;Maluf et al, 2005). Close genetic proximity was observed among the existing traditional commercial varieties in Kenya, namely SL28, SL34 and K7.…”
Section: Discussionmentioning
confidence: 66%
“…Whether this difference was due to the number of tested samples or the actual genetic diversity of the cultivars needs to be examined with a larger number of cultivars. However, Maluf et al (2005) reported that SSR markers are more effective in detecting genetic diversity than other markers, indicating that the findings in the present study may be used effectively in the future for analyzing the diversity of ginseng genetic resources.…”
Section: Ssr Polymorphismmentioning
confidence: 73%